Implementation of Inquiry Learning Model in Improving Students' Understanding of Islamic Values - Febrianto, Febrianto; Syafruddin, Syafruddin; Jamilah, Sri (Yayasan Indonesia Emerging Literacy Education, 2025)
This research aims to evaluate the effectiveness of the inquiry learning model in increasing students' understanding of Islamic values ​​in Madrasah Aliyah class XI Darul Hikmah Islamic Boarding School, Bima City. The research results show that the application of the inquiry learning model significantly increases students' understanding of Islamic values, such as honesty, loyalty and compassion. Through this approach, students are actively involved in the learning process, from formulating questions to finding solutions through group discussions. Inquiry learning encourages students to think critically, connect Islamic teachings with the social issues students face, and deepen students' understanding of Islamic teachings holistically. Although this model is effective, research also identifies several obstacles, such as limited teacher skills, limited learning time, and limited facilities and resources. This research suggests the need for collaborative efforts between teachers, students and madrasas to overcome these obstacles and increase the application of inquiry learning. These findings provide an important contribution to the development of inquiry-based learning models in Islamic religious education.